Material Imageability: The Architecture of Façades and Envelopes. (1st March 2023) - Brownell, Blaine
Abstract: Orchestrating façades and fenestration has become a much elevated art in contemporary California. Highly articulating the way a building faces onto the street is an expertise of Oakland‐based architect Thom Faulders. Blaine Brownell, architect, educator and researcher in emergent materials, examines Faulders Studio's recent oeuvre and its audacious and attractive material expression.